2016
DOI: 10.18632/oncotarget.10222
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of eukaryotic translation initiation factor 3H is associated with proliferation, invasion and tumorigenicity in human hepatocellular carcinoma

Abstract: AimWe studied the role of eukaryotic translation initiation factor 3 subunit H (EIF3H) in hepatocellular carcinoma (HCC) progression.ResultsHigh EIF3H expression was observed in 50.23% patients. Upregulation of EIF3H is an independent predictor for greater rates of cancer recurrence and shorter overall survival in HCC patients. Knockdown of EIF3H expression in HCC cells promoted apoptosis, and inhibited cell growth, colony formation, migration, as well as xenograft growth. TGF-βand MAPK pathways are potentiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…At the protein level, eIF3e affects proliferation and survival of glioblastoma cells (Sesen et al, 2014), is involved in colon tumor progression (Li et al, 2014) and breast tumor formation, (Suo et al, 2015) progression (Grzmil et al, 2010) and metastasis (Gillis and Lewis, 2013). High levels of eIF3h maintain the malignancy of several cancer cell lines in vitro (Zhang et al, 2008) and have been indeed observed in breast, prostate and hepatocellular carcinomas (Hershey, 2015; Zhu et al, 2016). How the targeting of these initiation factors help to explain superior activity of CM16 against cancerous over non-cancerous cells remains to be investigated.…”
Section: Discussionmentioning
confidence: 94%
“…At the protein level, eIF3e affects proliferation and survival of glioblastoma cells (Sesen et al, 2014), is involved in colon tumor progression (Li et al, 2014) and breast tumor formation, (Suo et al, 2015) progression (Grzmil et al, 2010) and metastasis (Gillis and Lewis, 2013). High levels of eIF3h maintain the malignancy of several cancer cell lines in vitro (Zhang et al, 2008) and have been indeed observed in breast, prostate and hepatocellular carcinomas (Hershey, 2015; Zhu et al, 2016). How the targeting of these initiation factors help to explain superior activity of CM16 against cancerous over non-cancerous cells remains to be investigated.…”
Section: Discussionmentioning
confidence: 94%
“…(30) At the chromosome 15 locus, Eif3h, encoding the eukaryotic translation initiation factor, is a candidate that is involved in the cell cycle. (31) One limitation of our study is that all F1 mice carry one chromosome from C57BL/6J and one chromosome from the HMDP. Thus, recessive risk alleles not present in the C57BL/6J genome will not be detected and mapped under our mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Fuca1 encodes the lysosomal hydrolase α‐L‐fucosidase implicated in cell growth and signaling . At the chromosome 15 locus, Eif3h, encoding the eukaryotic translation initiation factor, is a candidate that is involved in the cell cycle . One limitation of our study is that all F1 mice carry one chromosome from C57BL/6J and one chromosome from the HMDP.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first description of a germline CNV involving EIF3H gene. Indeed, only somatic copy number gains and over‐expression of this gene in several cancers were reported . While EIF3H somatic mutations/deletions are rare in tumors, COSMIC database registers copy‐number gains in more than 700 samples and over‐expression in more than 1.300 samples including colon, liver, ovary, breast, eye and central nervous system tumors.…”
Section: Resultsmentioning
confidence: 99%